Vibration characteristics of rotor system with disk-shaft clearance-eccentric coupling faults. (February 2023) - Li, Zhinong; Qiao, Fang; Ma, Xingfu; Li, Yunlong; Wang, Fei
Clearance between the disk and shaft can lead to the aggravation of the system fault. To solve this problem, a disk-shaft dynamic model with the clearance-eccentric coupling faults is established by the finite element method. Based upon the model, the dynamic characteristics of the system with different influence factors such as clearance and rotating speed are acquired by comprehensive analysis. Meanwhile, the accuracy of the dynamic model is verified by experiment investigations. The results show that frequency components in the spectrum include the shaft's rotating frequency and high frequency multiplication components. And the sawtooth phenomenon from the trajectory diagram of disk center can be observed. With the increase of rotating speed, the disk-shaft contact stress and strain energy first decrease and then increase, while the speed difference of disk to shaft and vibration amplitude increase, and the number of high frequency multiplication components in the spectrum decreases gradually. Furthermore, with the increase of clearance, the stable values of the disk-shaft contact stress and strain energy decrease, while the vibration amplitude, the number of high frequency multiplication components and speed difference increase gradually, and the trajectory shape of disk center changes from closed circle to hollow ring.